Percepções de suportes organizacional e social no trabalho como antecedentes da percepção de saúde da organização - Moraes, Elton Ramos (2007)
The concept of organizational health had its origin in the organizational effectiveness definition, which was originated in the Fifties. Conceived as an expanded effectiveness , the concept of organizational health, recent in literature, is still in need of studies, which allow its definite implantation in the scope of organizational behavior, and mainly, studies that clarify its nature, antecedents and consequences. In the attempt of fulfilling part of this agenda, this study had as objective testing an explanatory model, which foresaw the perceptions of organizational and social support in the work, as being the antecedent to the perception of organizational health. The participants of this study were in its total 160 workers of several companies from the Triângulo Mineiro: 59,1% of participants from feminine gender and 40,9% from masculine gender, both with an average age of 28,9 years old and postgraduation as the most frequent degree of education. The instrument of data collection was composed by a questionnaire containing the three scales that were used to measure the perceptions of two factors of organizational health, three factors of social support in the work and the perception of organizational support. To achieve the proposed objective multivariate analyses have been carried through. The results of this study reveal that the main variable for both the factors of organizational health perception was the perception of organizational support. The impact of the perception of social support in the work was smaller than compared to that one. Implications of this study, as academic as applied, have been discussed and an investigation agenda was suggested.